Digital Promotion Strategy for SMEs Using Motion Graphics: A Case Study of Metro Snack - Meilani, Anis Kholif; Firmansyah, Ada Udi (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Metro Snack is a micro, small, and medium enterprise (MSME) engaged in the production of banana chips, a signature souvenir from Lampung. Amid the rise of the digital era, the demand for creative and innovative promotional tools has become crucial for broadening market reach and enhancing competitive edge. This research seeks to develop animation-based promotional material employing motion graphics techniques through the Multimedia Development Life Cycle (MDLC) framework, encompassing stages such as concept formulation, design, material gathering, production, testing, and distribution. The development process utilized software including Canva for crafting visual components like logos and preliminary designs. It also used FlipaClip for creating 2D animations depicting banana chip production stages, and CapCut for video editing, incorporating visual effects, music, and narration. The outcome is a 1-minute 32-second promotional video that effectively showcases the unique strengths of Metro Snack’s products in an engaging and clear manner. This video has been uploaded to Instagram (@metro_snack_) with plans for expansion to other digital platforms. Findings indicate that motion graphics-based promotional videos boost brand awareness by up to 30% within the first month following distribution, as evidenced by social media engagement metrics such as likes and comments. This study aims to serve as a reference for other MSMEs in leveraging digital marketing strategies to strengthen competitiveness and drive sales growth.